A Monte Carlo study of the rough-sea-surface influence on the radar scattering from two-dimensional ships. - Burkholder, Robert J. (IEEE Antennas & propagation magazine.)
The generalized forward-backward (GFB) method was introduced in Pino et al. (1999) for computing the electromagnetic scattering from two-dimensional targets on a rough surface. The GFB method is used in this article to generate numerical data for a Monte Carlo simulation of the horizontally polarized radar cross section (RCS) of two-dimensional ship-like targets on random rough sea surfaces. The RCS is computed as a function of the incidence angle and wind speed for a large number of surface realizations. It is found that the mean RCS of a given target on a rough surface is generally lower than or equal to the RCS of the same target on a flat surface, while the maximum RCS is usually greater than or equal to the flat-surface case. It is also observed that the variations in the RCS introduced by the rough surface become less significant as the elevation angle approaches grazing.